IMPLEMENTASI ISLAMIC MARKETING MIX PRODUK TABUNGAN iB HIJRAH PRIMA PADA BANK MUAMALAT KANTOR CABANG PEMBANTU MADIUN - Pradana, Aldo Robby; Sofianiyatin, Lilik; Sulistia Ningsih, Linda (Fakultas Ekonomi Bisnis Islam, 2023)
This research aims to determine the obstacles and efforts in the Islamic Marketing Mix strategy in the Prima Savings product. The research was conducted using descriptive qualitative methods which aim to provide a systematic overview of the research focus which includes Islamic marketing mix strategies and prime savings products. The research subjects consisted of six informants. Data analysis is carried out to simplify data processing, so that readers can interpret and read easily. Data collection was carried out using interview and documentation techniques. Meanwhile, analysis of the data was carried out using the stages of data collection, reduction, presentation and verification. The results of this research show that the implementation of the Islamic Marketing Mix has an influence on the Prima Savings product at the Muamalat KCP Madiun Bank. This can be seen in the number of customers using prime savings products over the last five years. So it can be concluded that the application of the IMM strategy to the Prima Savings product at the Muamalat KCP Madiun bank can improve the product so that it can attract customer interest in opening the Prima Savings product.